Esophagus, stomach, duodenum and lesions - Campodónico, Esteban (1923)
The esophagus, radiologically considered, is the channel that runs from the junction pharyngeal esophageal cardia, esophagus does not follow a straight line with the head of the joint pharyngeal esophageal cardia, but undergoes some slight deviations, and first in its origin at the level of the cricoid cartilage; After you head slightly to the left again to reach the midline, then to deviate from the midline at the level of the aortic arch. Then goes through the left bronchus; goes through the diaphragmatic hiatus to conclude later in the cardia. These deviations, which apparently significangran thing without embardo for the radiologist are very important, because the points in which the deviations are checked are precisely the points a little closer and need preferably alert the radiologist of the strangest bodies they are housed in well under item nosologically, as we shall see later.